TOURISM COMPONENTS AND COMMUNITY PARTICIPATION TOWARD ECO -TOURISM SUSTAINABILITY IN CHON BURI PROVINCE - Narkwong, Thatdao; Krutwong, Amporn (Academic Journal of Thailand National Sports University, 2022)
Results were found that: - Overall of the opinion of tourism components of tourists toward eco-tourism sustainability in Chon Buri was in the highest level. When considering each item, the priority item was the tourism attraction, and then the tourism services, transport route, accommodation facility, and activities respectively. Overall of the community participation of people in Chon Buri was in the highest level. When considering each item, the priority item was the presentation idea and making decision, and then cooperation, monitoring and evaluation respectively. 3. Tourism components of tourists toward eco-tourism sustainability in Chon Buri were found at the significant difference level of .05. Meanwhile, the community participation toward eco-tourism sustainability in Chon Buri was found at the significant difference level of .05.